Glutamine synthetase activity and root induction in callus and cell suspension cultures of Vigna radiata (L.) R. Wilczek grown under different nutritional conditions - Khan , Amir Muhammad; Gilani, Syed Aneel (Journal of Pure and Applied Agriculture, 2025)
The activity of enzyme Glutamine Synthetase (GS) was studied in the cell suspension cultures of Vigna radiata grown under normal MS (Murashige & Skoog) medium and different nutritional deficient media i.e., nitrate (NO3) deficient, ammonia (NH4) deficient and glycine deficient media to study the behaviour of two weeks and four weeks old cultures. The objective of this study was to assess the metabolism of nitrogen assimilation for the production of cell lines which are more productive and high yielding. In this study, maximum GS activity was observed in the cell suspension culture of normal MS medium (26.8±0.86) and minimum in that of ammonia deficient medium (17.9±0.38). The GS activity was higher in the culture of two weeks duration viz. 26.8±0.86, 24.0±0.42, 17.9±0.38 and 23.5±0.98 as compared to that of four weeks cultures as 24.7± 2.14, 21.8±1.54, 16.7±1.31, and 23.2±0.38, respectively for normal, NO3, NH4 and Glycine deficient media. Root induction was observed in both the callus and cell suspension cultures, which further highlights the potential for propagating more productive and high-yielding cell lines. The same hormonal concentrations used for callus initiation were employed for cell suspension cultures. These included 2,4-D (0.2 mg/l), IAA (0.25 mg/l), and Kn (0.25 mg/l), which also facilitated root induction in both culture types. These results provide valuable insights into optimizing culture conditions for the production of high-yielding and productive cell lines, which is crucial for future agricultural and biotechnological applications.